ANALISIS RISIKO USAHATANI PADI RAWA LEBAK DI KECAMATAN BRAJA SELEBAH KABUPATEN LAMPUNG TIMUR - Rahayu, Esti Puji; Trisnanto, Teguh Budi; Unteawati, Bina (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
Utilization of lebak swamp land for rice production is one of the government's efforts to increase rice production in East Lampung Regency. Rice farming carried out on lebak swampland has a greater risk than the risk for rice farming carried out on paddy fields. Especially in Braja Selebah District which is a buffer zone for elephant breeding forest areas. The purpose of writing this final project is to identify farming risks, calculate the level of production risk and the risk of rice farming income on lebak swamp land in Braja Selebah District, East Lampung Regency. The data collection method used was simple random sampling with 30 respondents. The data used is data for 1 planting season, namely 2021. The types of data used are primary data and secondary data. The data analysis method used is a descriptive method and a quantitative method using the coefficient of variation (CV). Rice farming on lebak swamp land in Braja Selebah District has a high level of risk both from production risk and income risk, the types of risks that occur are production risk, price risk and income risk.